2014
DOI: 10.1227/neu.0000000000000533
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Outcome in Traumatic Brain Injury

Abstract: Use of the novel Helsinki CT score improved outcome prediction accuracy, and the Helsinki CT score is a feasible alternative to the Rotterdam and Marshall CT systems. External validation of the Helsinki CT score is advocated to show generalizability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 47 publications
2
98
0
1
Order By: Relevance
“…Another study comparing the M-CT and R-CT in a side-by-side manner found AUCs of 0.63 and 0.68 for 6 months unfavorable outcome and AUCs of 0.64 and 0.7 for 6 months mortality; the reported Nagelkerke's R 2 s were 0.09 and 0.16 for the prediction of 6 months unfavorable outcome and 0.09 and 0.15 for the prediction of 6 months mortality. [16] The performance indices reported in this study are similar to our findings and in favor of their comparability speaks the virtually the same line of statistical analysis that was followed in both studies (including optimism correction).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Another study comparing the M-CT and R-CT in a side-by-side manner found AUCs of 0.63 and 0.68 for 6 months unfavorable outcome and AUCs of 0.64 and 0.7 for 6 months mortality; the reported Nagelkerke's R 2 s were 0.09 and 0.16 for the prediction of 6 months unfavorable outcome and 0.09 and 0.15 for the prediction of 6 months mortality. [16] The performance indices reported in this study are similar to our findings and in favor of their comparability speaks the virtually the same line of statistical analysis that was followed in both studies (including optimism correction).…”
Section: Discussionsupporting
confidence: 88%
“…Both, the M-CT and the R-CT, have been proven as valid tools for prognosis of patients after TBI. [1516]…”
Section: Introductionmentioning
confidence: 99%
“…CT is consistently done on the day of injury (DOI), and then may or may not be repeated during the patient’s hospital stay. Scoring systems using CT findings such as the Marshall classification [6], the Rotterdam score [7], and most recently, the Helsinki score [8] have been developed, but these have primarily been found to be useful as predictors of mortality, as opposed to predicting long-term function. A limitation of the studies is that they primarily utilize a categorical CT abnormality classification system that relies heavily on neuroradiologist report, rather than direct examination of CT scans.…”
Section: Introductionmentioning
confidence: 99%
“…All admission head computerized tomography (CT) scans were classified by two authors (R.R, R.K). [1718]…”
Section: Methodsmentioning
confidence: 99%
“…The included covariates were age, the Glasgow Coma Scale (GCS) motor score, pupillary light reactivity, hypoxia, hypotension, hemoglobin, glucose, and the Helsinki CT score. [1518] The results from the logistic regression model are presented as odds ratios (OR) with 95% confidence intervals (CI).…”
Section: Methodsmentioning
confidence: 99%